2021
DOI: 10.3390/su132111734
|View full text |Cite
|
Sign up to set email alerts
|

Sargassum-Modified Asphalt: Effect of Particle Size on Its Physicochemical, Rheological, and Morphological Properties

Abstract: The effect of sargassum particle size on the final properties of sargassum-modified asphalt is investigated in this article. Seaweed sargassum particles were first obtained and characterized through elemental analysis, thermogravimetric analysis (TGA), X-ray diffraction, and FTIR spectroscopy. Additionally, pure and sargassum-modified asphalt blends were evaluated through physical and rheological tests such as penetration, softening point, thermal stability, dynamic viscosity, failure temperature, and epifluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Also, for PP-2S and PP-10S composite spectra, in addition to the signals attributed to PP, it is possible to identify the presence of signals attributed to OH and C=O groups at 1700 and 1630 cm −1 and at 1260 cm −1 from carboxylic groups present in hemicellulose, cellulose, and lignin present in Sargassum signals. This corroborates the presence of Sargassum particles in the PP matrix [29][30][31][32].…”
Section: Characterization By Ftirsupporting
confidence: 84%
“…Also, for PP-2S and PP-10S composite spectra, in addition to the signals attributed to PP, it is possible to identify the presence of signals attributed to OH and C=O groups at 1700 and 1630 cm −1 and at 1260 cm −1 from carboxylic groups present in hemicellulose, cellulose, and lignin present in Sargassum signals. This corroborates the presence of Sargassum particles in the PP matrix [29][30][31][32].…”
Section: Characterization By Ftirsupporting
confidence: 84%
“…In order to establish a proper mixing protocol for the algae-based blends, the relevant literature was considered [6,7,9,10]. It was observed that there was considerable variation among researchers regarding the mixing conditions for algae-modified bio-bitumen (Table 3).…”
Section: Mixing Conditionsmentioning
confidence: 99%
“…For instance, it was found that sargassummodified bitumen had higher viscosity and rutting resistance in comparison with unmodified petroleum-based bitumen, which could improve the high-temperature performance [6]. The same study indicated that a reduction in the sargassum particle size would bring about an increased specific surface area and thus better cohesion [6]. Furthermore, as the particle size is reduced, the storage instability of bitumen is also reduced up to 3% content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation